The Effect of Mannihot Esculenta on Prolactin Hormone Levels and Breast Milk Production in Breastfeeding Mothers: Efek Mannihot Esculenta pada Tingkat Hormon Prolaktin dan Produksi Susu Ibu pada Ibu Menyusui - Sherin Sausan Wulandari; Krisdiana Wijayanti; Lanny Sunarjo (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To prove the effect of cassava leaves jerky(Mannihot Esculennta) on prolactin hormone levels andbreast milk production in breastfeeding mothers in theWorking Area of the Rejosari Health Center of PekanbaruCity.Methods: This study used True Experiment Design with apretest and posttest design with the control group, usinga simple random sampling with a total of 28 breastfeedingmothers, 14 intervention group respondents, and 14 controlgroup respondents. The intervention group was givencassava leaves jerky 60 gr/day, and the control group wasgiven jerky without cassava leaves 20 gr/day for 2 weeks.Both groups were observed 3 times by weighing the baby'sweight and checking the level of the hormone prolactin afteradministering the intervention using the ELISA method. Dataanalysis using Mann-Whitney, TIndependent, RepeatedANOVA test.Results: There was a difference in the average differenceof prolactin hormone levels in the intervention group andcontrol group with a p-value of 0.000 (<0.05)Conclusion: Giving jerky cassava leaves breast milk boosteraffects the hormone prolactin and breast milk production inbreastfeeding mothers.Keywords: breast milk production, cassava leaves, mannihotesculenta, prolactin.Abstrak Tujuan: Untuk Membuktikan dendeng daun singkong(Mannihot Esculennta) terhadap kadar hormon prolaktindan produksi ASI pada ibu menyusui di Wilayah KerjaPuskesmas Rejosari Kota Pekanbaru.Metode: Penelitian ini menggunakan rancangan percobaanyang sebenarnya dengan desain pretest and posttest onlywith control group, sampling menggunakan sampel acaksederhana dengan jumlah 28 responden ibu menyusui,14 responden kelompok intervensi, dan 14 respondenkelompok kontrol. Kelompok intervensi diberi dendeng daunsingkong 60 gr/hari, dan kelompok kontrol diberi dendengtanpa daun singkong 20 gr/hari selama 2 minggu. Keduakelompok diamati sebanyak 3 kali dengan menimbangberat badan bayi dan pemeriksaan kadar hormon prolaktinsetelah pemberian intervensi dengan metode ELISA. Analisisdata menggunakan uji Mann-Whitney, TIndependent,Repeated ANOVA.Hasil: Terdapat perbedaan rata-rata selisih kadar hormonprolaktin pada kelompok intervensi 376,5 ng/ml, kelompokkontrol 103,5 ng/ml dengan p-value 0,000 (<0,05)Kesimpulan: Pemberian dendeng penambah ASI daunsingkong berpengaruh terhadap hormon prolaktin danproduksi ASI pada ibu menyusui.Kata kunci: daun singkong, mannihot esculenta, produksiASI, prolaktin.